2015
DOI: 10.1186/s13046-015-0228-4
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib-induced antitumour activity in human alveolar rhabdomyosarcoma cells is not solely dependent on ALK and MET inhibition

Abstract: BackgroundRhabdomyosarcoma (RMS) is the most commonly diagnosed malignant soft tissue tumour in children and adolescents. Aberrant expression of Anaplastic Lymphoma Kinase (ALK) and MET gene has been implicated in the malignant progression of RMS, especially in the alveolar subtype. This observation suggests that crizotinib (PF-02341066), a kinase inhibitor against ALK and MET, may have a therapeutic role in RMS, although its antitumour activity in this malignancy has not yet been studied.MethodsRH4 and RH30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 58 publications
6
43
0
Order By: Relevance
“…Further, the cell cycle analysis showed a G1 arrest after erlotinib (Giovannetti et al, 2008;Huether, Höpfner, Sutter, Schuppan, & Scherübl, 2005) and a G2/M arrest after crizotinib (Megiorni et al, 2015), which is in accordance with the literature. However, after the combination, the effect of crizotinib was dominant but weaker than after the monotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Further, the cell cycle analysis showed a G1 arrest after erlotinib (Giovannetti et al, 2008;Huether, Höpfner, Sutter, Schuppan, & Scherübl, 2005) and a G2/M arrest after crizotinib (Megiorni et al, 2015), which is in accordance with the literature. However, after the combination, the effect of crizotinib was dominant but weaker than after the monotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study reported that crizotinib increases intracellular ROS levels in human alveolar rhabdomyosarcoma and embryonal rhabdomyosarcoma cells [ 13 ]. Therefore, we evaluated the generation of intracellular ROS by measuring oxidized DCFH-DA (2′,7′-dichlorodihydrofluorescein-DA), and tested whether crizotinib induces apoptosis in Ba/F3 cells expressing NPM-ALK through the generation of ROS.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms by which crizotinib exhibits its anti-tumor activity against various tumors harboring the mutation in ALK genes currently remain unclear. A recent study reported that a treatment with crizotinib resulted in the accumulation of reactive oxygen species (ROS) in human alveolar rhabdomyosarcoma and embryonal rhabdomyosarcoma cells [ 13 ], suggesting that crizotinib exhibits anti-tumor activity through the generation of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the structural similarity of the tyrosine kinase domains across RTK families, most tyrosine kinase inhibitors lack specificity compared to monoclonal antibodies. While therefore being less suitable when studying specific RON functions, a broader target spectrum comprising RON among other, more-established RTK targets (including its interacting co-targets MET and IGF1R [6,47]) may promote the clinical development of tyrosine kinase inhibitors, such as crizotinib (NCT02612194) or ASLAN002 (also known as BMS-777607; NCT01721148) [48].…”
Section: Targeting Ron With the Imc-ron8 Antibody Strategymentioning
confidence: 99%